دور الرقابة النظامية على الصفقات العمومية في تحقيق الحوكمة على المؤسسات العمومية دراسة ميدانية بمديرية الأشغال العمومية – سوق أهراس- - غادة سحتوت (My University, 2022)
The study aims to identify the various concepts that relate to public transactions, as well as to try to understand the governance of public institutions and to learn about the principles related thereto, and how to monitor public transactions in Algeria by emphasizing the reflection of the governance principles of equality, transparency and competition and ensuring a balance of interests. In the study, we relied on the curriculum on the descriptive analytical curriculum to cover both the theoretical and the applied aspect of our approach to the Directorate of Public Works -Souk-ahras-, through the study of the acquisition project and the placement of 945 km of horizontal signals on national roads to describe all matters relating to the control of public transactions and governance over public institutions in Algeria, as well as the procedures set out in the Law on Public Transactions 15-247. The study produced a series of findings, the most important of which were public transactions based on the governance principles of free access to public demand, equal treatment of candidates and transparency of procedures. The study affirmed that the contracting interests are committed to applying the principles of governance to conclude and implement public transactions in the Directorate of Public Works – souk-ahrass - nor are they without any impediments. ................................................. تهدف الدراسة إلى تبيان مختلف المفاهيم التي تتعلق بالصفقات العمومية، وكذا محاولة فهم حوكمة المؤسسات العمومية والتعرف على المبادئ المتعلقة بها مع بيان كيفية الرقابة على الصفقات العمومية في الجزائر من خلال التأكيد على تجسيد مبادئ الحوكمة المتمثلة بالمساواة والشفافية والمنافسة وضمان توازن المصالح. واعتمدنا في الدراسة على المنهج التحليلي الوصفي، لتغطية كل من الجانب النظري والتطبيقي الذي توجهنا به إلى مديرية الأشغال العمومية -سوق أهراس- وذلك من خلال دراسة مشروع اقتناء ووضع 549 كلم من الإشارات الأفقية على الطرق الوطنية لوصف كل ما يتعلق بالرقابة على الصفقات العمومية والحوكمة على .742- المؤسسات العمومية في الجزائر وجملة الإجراءات التي ينص عليها قانون الصفقات العمومية 59 وقد توصلت الدراسة إلى مجموعة من النتائج أهمها تقوم الصفقات العمومية على مبادئ الحوكمة المتمثلة في حرية الوصول للطلب العمومي، المساواة في معاملة المترشحين، وشفافية الإجراءات. أكدت الدراسة أن المصالح المتعاقدة تلتزم بتطبيق مبادئ الحوكمة لإبرام وتنفيذ الصفقات العمومية في مديرية الأشغال العمومية –سوق أهراس- كما أنها لا تخلوا من جملة من المعوقات.